The Effect of Hepatitis B Vaccine on Health Workers in Medina - Rayan Talaat Karali; Faridah Mohd Said; Khalid Homod Algaydi; Abdulrahman G. Alharbi; Adel Muslim Alharbi; Mohammed Abdullah Alharbi; Basmah Meqbel Alharbi; Majed Ghali Alharbi; Bader Awad Almohammadi; Khalid Adnan Shujaa; Ahmed Fahed Alanazi; Abdullah Ghali Alharbi (Academia Open, 2024)
This study aimed to assess hepatitis B virus (HBV) vaccination rates among healthcare professionals and understand their knowledge about HBV transmission. Conducted in a healthcare setting, the research employed survey methods to collect data on vaccination status and awareness levels. Alarmingly, only 25% of healthcare workers were found to be vaccinated against HBV, highlighting a significant gap in protection. Additionally, a considerable lack of awareness regarding HBV transmission was observed among the participants. These findings underscore the urgent need for targeted vaccination campaigns and educational initiatives within primary healthcare environments. The study advocates for mandatory HBV vaccination as a condition of employment for healthcare workers, coupled with ongoing infection prevention and control training. Further research is recommended to explore the prevalence of HBV infection among healthcare professionals in primary care settings and to assess the broader implications for public health. This study serves as a critical call to action for healthcare systems to prioritize HBV vaccination and education, thereby safeguarding both healthcare providers and patients from HBV infection risks. Highlights : Low Vaccination Rates: Only 25% of healthcare workers are vaccinated against HBV, indicating a critical need for improved vaccination coverage in healthcare settings. Knowledge Deficit: There is a significant lack of awareness among healthcare professionals about HBV transmission, necessitating educational programs. Policy Implications: The study advocates for mandatory HBV vaccination for healthcare workers, emphasizing the importance of infection control measures for public health safety. Keywords : Hepatitis B Vaccination, Healthcare Workers, Infection Prevention, Public Health, Vaccination Awareness